ORIGINALITY OF LINA KOSTENKO’S LANDSCAPE LYRICS (POETRY OF SECTION «WANTING MIRACLE AND A BIT OF WINE» COLLECTION OF «TREE HUNDRED POETRIES») - Tetyana V. Filat (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2019)
In the article the specificity and ethical-philosophical basis of the landscape lyric of Lina Kostenko are discussed, the poetics of the embodiment of the ideologic and imaginative structure of this genre variety, the traditional and innovative features of the lyrical poems of the section “Wanting Miracle and a Bit of Wine” from the collection “Three hundred poetries” are highlighted. In the analyzed section, sharp observation of the poet’s skills, a spiritual understanding of the nature as an ethical-philosophical category appear. Lina Kostenko’s poetic dictionary of poems is typical for the national landscape of Ukraine. Nomination of seasons (spring, summer, autumn), flora (field and ornamental flowers, bushes, trees, forest, gardens) act as prop words. As it has already been denoted, the forest is one of the favorite supporting symbols of landscape lyrics, which image most commonly appears as a metaphor relating the wood to the man. The poetess introduces the names of various trees, representative for the Ukrainian woodland landscape (pine, oak, osier, rowan-tree, birch, poplar, viburnum, pear-tree). In addition to the characters of national flora, predominant in the poetess’ landscape lyrics, the representatives of Ukrainian fauna are introduced as well. The fauna represents typical animals living on the territory of Ukraine (bear, squirrel, horse, elk, hare, birds, fish, etc.). Astronomical objects (the sky, the sun, the moon), meteorological phenomena and elements (wind, thunder, rain, fog, fire), as well as objects of the earth’s surface (river, lake, coast, mountains) appear in the perception of a lyrical subject. The listed landscape components, their natural features are not isolated in the perception of the hero but are uniquely combined in the lyrical understanding of beauty. Nature is not alienated from the hero, but organically merged with him. Poetess unites picturesque visualization of landscape, recreating acute obviousness of lyric subject, with the transference of its emotions, originated by special organic connection with native Ukrainian nature, most often based on their harmonic unanimity. The Nature is not hostile, not antonymic to the lyric subject, and it occurs in harmonic connection between it and the sphere of its perception, where lyric subject does not act like the observer, it is organically associated with the nature. The same flora and fauna details of landscape generate its diverse feelings and associations, shared with the readers. L. Kostenko’s subject of landscape lyrics outstands as a humanist, a patriot, an intellectual, an adept not only of the national literature, but of the foreign one as well. The theme of a human and nature harmony dominates in Lina Kostenko’s landscape lyrics. The poetess singles out environmental issues as a central one, focusing on the aspect of the relationship between the nature and society, which destroys it from mercenary motives.